Retinal detachment : principles and practice - Brinton, Daniel A., 1955-; Wilkinson, C. P.; Hilton, George F. Retinal detachment; American Academy of Ophthalmology (New York, NY. : Oxford University Press, Inc., 2009)
Includes bibliographical references and index.